Koala conservation in South East Queensland: a shared responsibility. Issue 1 (2nd January 2023) - Tkaczynski, Aaron; Rundle-Thiele, Sharyn
ABSTRACT: The koala (Phascolarctos cinereus) is an iconic Australian animal. Its recent reclassification to endangered in locations such as South East Queensland, New South Wales and the Australian Capital Territory indicates urgent and further conservation actions are required. This article proposes that a downstream social marketing approach can be applied to encourage South East Queensland residents to take preventative actions to protect koalas in their region. This article reports the results of an online survey that was completed by 2, 592 South East Queensland residents. The data was cluster analysed using TwoStep cluster analysis, resulting in three valid segments. Active koala enthusiasts are knowledgeable and active in koala conservation. City residents were aware of koalas' decline but are unfamiliar with conservation actions. Young dog owners do not know about the decline of koalas and they do not currently perform conservation actions. Respondents agreed that koala conservation is a shared responsibility between residents, organisations and governments and too many are not aware of actions they can take. Tailored approaches should be applied in the future, including citizen science initiatives such as completing online koala sightings to broaden understanding of koala habitats.